Engineered exosomes derived from miR-132-overexpresssing adipose stem cells promoted diabetic wound healing and skin reconstruction - Ge, Lifeng; Wang, Kangyan; Lin, Hang; Tao, Endong; Xia, Weijie; Wang, Fulin; Mao, Cong; Feng, Yongzeng (Frontiers in Bioengineering and Biotechnology, 2023)
The tissue reconstruction of diabetic wounds mainly depends on the proliferation and remodelling of cutaneous cells around wounds and the transplantation of random skin flaps, however, the proliferation of cells or survival of skin flaps are difficult due to the severe inflammation and other problems caused by diabetes. The stem cell-derived exosomes loaded with miRNA can be an effective therapeutic strategy for promoting diabetic wound healing. Therefore, in this study, the engineered exosomes derived from miR-132-overexpressing adipose stem cells (miR-132-exo) was obtained for promoting the healing of diabetic wounds and skin flaps. In vitro, the miR-132-exo promoted the proliferation and migration of human umbilical vein endothelial cells (HUVECs). In vivo, streptozotocin (STZ) induced diabetic mice were used to create full-thickness skin wounds and random skin flaps to further investigate the healing effect of miR-132-exo. The results showed miR-132-exo evidently enhanced the survival of skin flaps and promote diabetic wound healing, through reducing local inflammation, promoting angiogenesis and stimulating M2-macrophages polarization mediated by NF-κB signaling pathway. These novel findings demonstrated that engineered miR-132-exo can be a potent therapeutic for treating diabetic wounds and inflammatory-related disease.